Uptake of intermittent preventive treatment of malaria in pregnancy and risk factors for maternal anaemia and low birthweight among HIV-negative mothers in Dschang, West region of Cameroon: a cross sectional study - Kamga, Sabrina Lynda Simo; Ali, Innocent Mbulli; Ngangnang, Ghislain Romeo; Ulucesme, Mehmet Can; Keptcheu, Leonard T. D.; Keming, Eva Mai; Payne, Vincent K. (Bmc, 2024)
Background Approximately 32 million pregnant women are at risk of malaria with up to 10,000 maternal deaths and 200,000 neonates at risk annually. Intermittent Preventive Treatment (IPT) with sulfadoxine-pyrimethamine (SP) is recommended by the World Health Organization (WHO) to reduce disease in pregnancy and adverse maternal and newborn outcomes. At least three doses of SP should be taken by pregnant women during antenatal consultation (ANC) beginning from the thirteenth week of pregnancy till parturition. The aim of this study was to assess uptake of IPT during pregnancy and risk factors for maternal anaemia and infant birth weight in Dschang, West region of Cameroon. Methods A total of 380 consenting pregnant women at delivery were recruited in a cross- sectional prospective survey between January to December 2021. Data on ANC attendance, total dose of IPT and history of malaria were abstracted from hospital ANC records while socio-demographic characteristics, bed net use and obstetrics history of each participant were also recorded through an interview. Further, blood samples were collected from the intervillous space for assessment of maternal anaemia and microscopic parasitology. Nested PCR based on amplification of the Plasmodium 18S sRNA was carried out to detect submicroscopic infection. IPTp coverage was calculated per WHO recommendation and the prevalence of anaemia and low birth weight were estimated as proportions in the total sample of pregnant women and live births, respectively. Crude and adjusted odds ratios and their 95% confidence intervals were used to estimate associations between pregnancy outcomes considered and risk factors in specific and general models. A p < 0.05 was considered significant. The R software (V4.1.4) was used for all analyses. Results A majority of pregnant women was aged between 24 and 34 years old (59.2%) and had secondary education (58.8%). Uptake of >= 3 IPTp was 64.99% with 77.20% of all who received at least one IPTp doses taking a mix of SP and DP or DP alone in successive ANC contacts. Those with four or more ANC contacts (73.42%) were more likely to have received at least one IPTp. Furthermore, 13.9% of live births had low birthweights (BW < 2500 g) and one in four parturient women with moderate anaemia by WHO criteria. Microscopy (blood smear examination) and PCR-based diagnosis revealed between 0% and 1.57% of parasite-infected placental samples, respectively. Reported malaria in pregnancy predicted maternal anaemia at birth but not birth weight. Only gestational age (< 37 weeks) and bed net use (< 5 months) significantly predicted infant birth weight at delivery. Conclusion The uptake of WHO recommended IPT doses during pregnancy was moderately high. Reported malaria in pregnancy, poor bed net coverage, gestational age less than 37 weeks adversely affect maternal haemoglobin levels at birth and infant birth weight. Asymptomatic and submicroscopic placental parasite infections was found at low prevalence. Together these results highlight the importance of maintaining aggressive measures to prevent malaria in pregnancy and protect the health of mother and baby.
Keywords: IPT; Birth weight; Maternal anemia; Malaria; Pregnancy; Dschang